Fraction Dominoes as Teaching Tools Using Sets in Mathematics Teaching - Muna, Trimurtini, Nur Aizatun (Universitas Negeri Semarang, 2018)
The objectives of this study were to develop a design, to determine the appropriateness and effectiveness of fractional dominoes with set approach. This type of study was Sugiyono's Research and Development (RD). One set of game consisted of three game devices. The game card had 2 parts; fractions and sets. The material expert assessment result was 96% and the media expert was 94% (very feasible). Furthermore, the learning outcomes showed that learning completeness reached 75%. The media produced an average difference (t-test) in the product test that was 6.1, input test was 10.64 and the learning outcomes enhancement (n-gain) in the product test was 0.8, input test was 0.76 (high). Thus, it could be concluded that the fractional dominoes game as a media with compilation approach on equivalent fraction in Mathematics subject matter of fourth-grade students was effective and feasible to use.